Identifikasi Sektor Ekonomi Unggulan di Daerah Tangkapan Air Danau Rawa Pening - Sigit Andy Cahyono; Faiqotul Falah; S. Agung Sri Raharjo (Department of Urban and Regional Planning, Diponegoro University, 2020)
Rawa Pening Lake is one of the priority lakes facing severe eutrophication and sedimentation problems. Agriculture is one of the problems in Rawa Pening Lake, even though community welfare is the government's policies. For this reason, the development of the economic sector in Rawa Pening catchment area must have advantages, yet information on this is still neglected and limited. The study aims to analyze the leading economic sectors in the Rawa Pening catchment area. The study used the Klassen Typology method to determine the pattern and structure of the economy and the Location Quotient method in determining the economic sector that has a comparative advantage in each sub-district and analysis of sectoral contributions. The data used is secondary data and field observations. The results showed that Bawen Subdistrict was a developed but depressed area, relying on the manufacturing industry sector. Rapidly developing districs (Tuntang, Jambu, Sumowono, and Ambarawa) rely on all economic sectors. The lagging districts (Getasan and Banyubiru) relly on the primary sector. Leading sectors of each district differ depending on resources and comparative advantage. Leading economic sector contribute relatively significantly to economic development in the lake Rawa Pening catchment. The development of the economic sector will be better directed to leading economic sector so that it can attract sector that are not base, especially in the limited resources and allocation of development budgets. In addition, Location Quotient analysis can be used for analysis of areas with natural boundaries such as catchments or watersheds.